Deteksi Gen blaZ pada Staphylococcus aureus Isolat Urine Pasien ISK Menggunakan Metode Real-Time PCR - Verdiani, Intan; Pestariati, Pestariati; Puspitasari, Ayu (Jurnal Laboratorium Khatulistiwa, 2025)
Urinary tract infection (UTI) is one of the most common bacterial infections and is often caused by various types of bacteria. In recent years, the prevalence of Staphylococcus aureus in UTI cases has increased, along with rising resistance to antibiotics, particularly the β-lactam group such as penicillin. This study aimed to detect the blaZ gene, which plays a role in penicillin resistance in S. aureus isolated from the urine of UTI patients. The study was conducted from November 2024 to May 2025 using a descriptive quantitative design. A total of 100 urine samples from UTI patients were obtained from RSPAL Dr. Ramelan Surabaya. Bacterial identification was carried out at the Microbiology Laboratory of RSPAL Dr. Ramelan using the Vitek 2 Compact system. Phenotypic resistance testing against penicillin G was performed at the Bacteriology Laboratory of the Department of Medical Laboratory Technology, Poltekkes Kemenkes Surabaya using the Kirby-Bauer disc diffusion method. Genotypic detection of the blaZ gene was conducted using the Real-Time PCR method at the Molecular Biology Laboratory. The results showed that out of five Staphylococcus aureus isolates phenotypically resistant to penicillin G, only three isolates (60%) were positive for the blaZ gene. These findings indicate that penicillin resistance in S. aureus is not solely mediated by the blaZ gene and highlight the importance of molecular surveillance of β-lactam resistance genes in clinical isolates.